Entrepreneurship of Poles in the light of changes in value systems - Gruszewska, Ewa (Annales. Etyka w Życiu Gospodarczym, 2019)
Poland’s transformation is occurring in individuals’ attitudes and behaviour. Several years ago, the entrepreneur was associated in Poland with corruption and borderline legal activities. Today, many entrepreneurs are looked upon as positive role models. Social acceptance of entrepreneurial attitudes in Poland is growing. Increased susceptibility to entrepreneurial behaviour in society will increase the rate at which new businesses are established, enhancing market dynamics and accelerating innovative changes. In Poland, however, entrepreneurs are not seen as a positive example, unlike in the United States. Willingness to take risks, selfexpression and independence are not met with social acceptance, especially if rewarded with high incomes. The research undertaken by the author is aimed at analysing the essence of entrepreneurial attitudes and changes in the social acceptance of entrepreneurial behaviour.